Preparation of Raney cobalt and identification of surface structures responsible for catalytic activity in the Fischer–Tropsch process. Issue 2 (26th October 2022) - Solomonik, I. G.; Gryaznov, K. O.; Mitberg, E. B.; Mordkovich, V. Z.
Abstract: A method for leaching Co2 Al9 alloy was developed and optimized to produce nonpyrophoric Raney cobalt, which is used as a component of a highly efficient granular Fischer–Tropsch synthesis catalyst. A comparative study of the laboratory‐produced Raney cobalt with commercially available analog was done using the methods of low‐temperature nitrogen sorption, thermoprogrammed reduction (TPR), thermoprogrammed ammonia desorption, thermal analysis, thermal conductivity, and scanning and transmission electron microscopy. Partial dissolution of cobalt with the formation of Co 2+ and Co 3+ ions was detected during aluminum leaching. It was found that incomplete purification of commercial Raney cobalt from aluminum hydroxide impurity may lead to overestimation of specific surface area. It was also found that the acidity of the molded catalyst is mainly determined not by Raney cobalt, but by elements of the composite catalyst carrier. For the first time, a linear dependence between the content of structures in a Fischer–Tropsch synthesis catalyst with TPR‐AR maxima of 500–800°C and the amount of synthesized liquid hydrocarbons has been established. It is concluded that metal nanoparticles with partial charge transfer (Co δ+ ) are active centers of selective formation of C5+ hydrocarbons. Obtaining the maximum number of these centers and reaching a high thermal conductivity of the composite with a developed system of transport pores is a criterion for creating an effective cobalt catalyst for low‐temperature synthesis of hydrocarbons. Abstract : An optimized method was developed for leaching Co2 Al9 alloy to produce Raney Co as a catalyst for industrial Fischer–Tropsch synthesis. The system was studied by a number of physicochemical methods. It was shown that Co δ+ nanoparticles are active centers of selective formation of C5+  hydrocarbons.